The association of acute kidney injury with hospital readmission and death after pediatric cardiac surgeryCentral MessagePerspective - Sophia Nunes, MSc; Jeremiah Brown, PhD, MS; Chirag R. Parikh, MD, PhD; Jason H. Greenberg, MD, MHS; Prasad Devarajan, MD; Heather Theissen Philbrook, PhD, MMath; Michael Pizzi, BSc; Ana Palijan, PhD, MS; Michael Zappitelli, MD, MSc (JTCVS Open, 2020)
Background: Acute kidney injury (AKI) in children undergoing cardiac surgery (CS) is strongly associated with increased hospital mortality and length of stay. The association of AKI with postdischarge outcomes is unclear. We evaluated the association of AKI with all-cause readmissions and death within 30 days and 1 year of CS discharge. Methods: This was a prospective, 3-center cohort study of children after CS with cardiopulmonary bypass. The primary exposures were postoperative ≥stage 1 AKI and ≥stage 2 AKI defined by Kidney Disease: Improving Global Outcomes AKI definition. Two separate outcomes were hospital readmission and death within 30 days and 1 year of discharge. Association of AKI with time to outcomes was determined using multivariable Cox-proportional hazards analysis. Age, The Society of Thoracic Surgeons-European Association for Cardio-Thoracic Surgery risk adjustment tool score ≥3, cardiopulmonary bypass >120 minutes, and cyanotic heart disease were evaluated as effect modifiers. Results: Of 402 participants included (median age 1.8 years [interquartile range 0.4, 5.2]), 32 (8.0%) and 109 (27.1%) were readmitted; 7 (1.7%) and 9 (2.2%) died within 30 days and 1 year of CS, respectively. AKI was not associated with readmission at 30 days or 1 year postdischarge. ≥Stage 2 AKI (adjusted hazard ratio, 11.68 [1.88, 72.61]) was associated with mortality 30 days post-CS. Conclusions: Postoperative AKI was not associated with readmission at 30 days and 1-year postdischarge. However, more severe AKI (≥stage 2) appears to be associated with increased morality risk at 30 days post-CS.